1988
DOI: 10.3171/jns.1988.68.4.0589
|View full text |Cite
|
Sign up to set email alerts
|

Imbalances in T cell subpopulations in human gliomas

Abstract: The quantitation of cells bearing CD3, CD4, CD8, and B cell phenotypic markers, as well as an estimation of serum immunoglobulin (Ig)G, IgA, and IgM, was carried out in a group of 39 glioma patients with different grades of malignancy. The findings were compared with those obtained from 21 normal healthy control subjects. The analysis revealed a significant decrease both in the absolute numbers and in the percentages of circulating CD3+ (p less than 0.001) and CD4+ (p less than 0.001) cells, while the CD8+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Gliomas seem to lack expression of TNF-a and, in fact, elaborate soluble TNF receptors which down-regulate infiltration of immune-competent cells (38). In addition, several studies have suggested that glioblastoma multiforme patients have T-cell dysfunction (39,40). However, this is not supported by the current study because glioblastoma multiforme patients were found to exhibit memory adenovirus-specific T-cell responses, functional dendritic cells, and tumor-specific T-cell responses.…”
Section: Discussioncontrasting
confidence: 79%
“…Gliomas seem to lack expression of TNF-a and, in fact, elaborate soluble TNF receptors which down-regulate infiltration of immune-competent cells (38). In addition, several studies have suggested that glioblastoma multiforme patients have T-cell dysfunction (39,40). However, this is not supported by the current study because glioblastoma multiforme patients were found to exhibit memory adenovirus-specific T-cell responses, functional dendritic cells, and tumor-specific T-cell responses.…”
Section: Discussioncontrasting
confidence: 79%
“…We found that GBM patients had lower levels of CD3 C T cells than controls, as in other reports, 34 and lower levels of CD4 C CD25 C T cells, but a trend toward higher numbers of Foxp3-positive T cells. GBM patients also had increased levels of CD4 C T cells that expressed CD57 but had lost CD28 expression, which may indicate increased proliferative instability and senescence.…”
Section: Discussionsupporting
confidence: 90%
“…Do these factors influence systemic immunocompetence? In glioma patients, peripheral lymphocyte counts (specifically CD3 + and CD4 + cells) were reduced in relation to healthy individuals as was pointed out by Bhondeley et al 1 recently. In our glioma patients, this finding holds true, even when it was not healthy volunteers but patients with benign extracerebral tumours who served as controls.…”
Section: Pathophysiologymentioning
confidence: 54%